Discrimination by Private Clubs - William G. Buss (Washington University Law Quarterly, 1989)
The fierce defense of a private right to discriminate in club membership, exemplified by Justice Douglas' Moose Lodge opinion, is one of the glories and contradictions of our constitutional system; and, as Virginia Woolf deftly observes, exercise of the right even in a seemingly benign form imposes real harm on those excluded. The paradigm case that I will be discussing grows out of the controversy that may occur when a private organization or association, which might loosely be called a "club," excludes from membership certain people because of their racial, ethnic, sexual, or religious identity. The legal and human problems presented by such a case involve a conflict between the interest in being treated equally and the interest in being free to choose one's own personal relationships. Converted to a clash of rights, under federal or state law, the paradigm case becomes a collision between a right to be free from discrimination and a "right to discriminate" stemming from freedom of association.
Keywords: Freedom of association